2008
DOI: 10.1128/mcb.01265-07
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor FOXO3a Increases Phosphoinositide-3 Kinase/Akt Activity in Drug-Resistant Leukemic Cells through Induction of PIK3CA Expression

Abstract: The phosphoinositide-3 kinase (PI3K)/Akt signal pathway plays a key role in the tumorigenesis of many cancers and in the subsequent development of drug resistance. Using the K562 chronic myelogenous leukemia (CML) cell line and the doxorubicin-resistant derivative lines KD30 and KD225 as models, we observed that enhanced PI3K/Akt activity and the acquisition of chemoresistance correlated unexpectedly with the increased expression and nuclear accumulation of FOXO3a. Moreover, we found that the induction of FOXO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
115
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 50 publications
14
115
0
Order By: Relevance
“…As a recent study showed that Akt overexpression decreases the chemosensitivity of gastric cancer cells to CDDP in vitro and in vivo [12], we investigated whether Akt is related to the FOXO1 regulation of CDDP cytotoxicity in gastric cancer cells. In the present study, constitutive activation and silencing of Our results agree with those of Hui et al [19], which showed FOXO3-induced PI3K/Akt activation in response to doxorubicin treatment of chronic myelogenous leukemia cells. However, our observations contrast with those of Gao et al [10], which demonstrated that FOXO1 enhanced CDDP cytotoxicity in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As a recent study showed that Akt overexpression decreases the chemosensitivity of gastric cancer cells to CDDP in vitro and in vivo [12], we investigated whether Akt is related to the FOXO1 regulation of CDDP cytotoxicity in gastric cancer cells. In the present study, constitutive activation and silencing of Our results agree with those of Hui et al [19], which showed FOXO3-induced PI3K/Akt activation in response to doxorubicin treatment of chronic myelogenous leukemia cells. However, our observations contrast with those of Gao et al [10], which demonstrated that FOXO1 enhanced CDDP cytotoxicity in ovarian cancer cells.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously shown that phosphorylated FOXO1 is overexpressed in gastric cancer specimens and that FOXO1 inactivation is related to better prognosis of gastric cancer patients [18]. Although FOXO proteins, especially FOXO1 and FOXO3, have been reported to be related to chemoresistance in various cancer cells [8][9][10][19][20][21], their involvement in chemoresistance of gastric cancer cells has not been reported. In the present study, we used two gastric cancer cell lines, MKN45 and SNU-601, with constitutive FOXO1 expression and found that CDDP treatment increased the levels of FOXO1 protein expression and activation.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that PIK3CA transcription is repressed by the tumor suppressor protein p53 in ovarian surface epithelial cells, and provided evidence to show that loss of p53 in ovarian cancer is one mechanism that leads to elevated p110a levels (Astanehe et al, 2008). In addition, it has recently been demonstrated that the forkhead transcription factor, FOXO3a, induces PIK3CA by directly binding to its promoter rendering chronic myelogenous leukemia cells resistant to doxorubicin (Hui et al, 2008). However, the induction of PIK3CA by FOXO3a is paradoxical as it is a known tumor suppressor with its activation mediating apoptosis in cancers including those of the breast (Sunters et al, 2003).…”
Section: Introductionmentioning
confidence: 71%
“…In line with this, FOXP1 expression is increased in colorectal cancer cells in response to treatment with the chemotherapeutic doxorubicin as well as after specific inhibition of PI3K-PKB signaling. We propose that similar to FOXO-induced HER3 and PIK3CA expression in response to cancer therapy aimed at inhibiting PI3K-PKB signaling, 14,16,47 FOXP1 possibly represents another mode of developing escape from treatment by protecting the cells against FOXO-induced cell death.…”
Section: Discussionmentioning
confidence: 99%